Immobilization of bile salt hydrolase enzyme on mesoporous SBA-15 for co-precipitation of cholesterol - Bhange, Pallavi; Sridevi, N.; Bhange, Deu S.; Prabhune, Asmita; Ramaswamy, Veda (International Journal of Biological Macromolecules, 2014)
We describe herein a simple and effective strategy for immobilization of bile salt hydrolase enzyme by grafting glutaraldehyde groups inside channels of APTES functionalized SBA-15. The increase in glutaraldehyde concentration prevents leakage of enzyme but showed a steep decrease in enzyme activity in the immobilized matrix. So the degree of cross-linking should be the minimum possible to ensure sufficient stability without loss of activity. Cross-linking carried out with 0.1% glutaraldehyde concentration showed the highest activity, so this was used in all further experiments. Physico-chemical characterizations of the immobilized enzyme were carried out by XRD, N-2 adsorption, TEM, FUR and Si-29 CP-MAS NMR techniques. Immobilized BSH exhibits enhanced stability over a wide pH (3-11) and temperature range (40-80 degrees C) and retains an activity even after recycling experiments and six months of storage. From our in vivo research experiment toward co-precipitation of cholesterol, we have shown that immobilized BSH enzyme may be the promising catalyst for the reduction of serum cholesterol levels in our preliminary investigation. Enhancement in pH stability at the extreme side of pH may favor the use of immobilized BSH enzyme for drug delivery purpose to with stand extreme pH conditions in the gastrointestinal conditions. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Bile salt hydrolase; Co-precipitation of cholesterol; SBA-15